023 Multiprofessional morning handover in the Emergency Department: is it effective?. (14th September 2011) - Lajko, K; Dev, S; Adshead, N
Abstract : Objectives and Backgrounds: Emergency Department (ED) handovers are arguably more complex than that which takes place in ward environments. This is because of an unpredictable patient load, compressed time-frames to meet operational and performance targets and undifferentiated and undiagnosed nature of the clinical problems. In order to ensure safe, relevant and accurate handovers in our department, we have implemented a novel multiprofessional model incorporating appropriate information exchange, learning opportunities and social interaction. In this study we investigated the effectiveness and usefulness of this new morning handover structure. Methods: A questionnaire containing 10 questions were given to staff over a 1-week period (14 to 20 March 2011). The questions included the following: (a) usefulness of multiprofessional handover (MPH) as a source of information about departmental and trust updates; (b) patient care and operational issues; (c) interprofessional education forum; and (d) comparison with previous handover experience. Results: We obtained data from 75 staff members comprising a mixture of the multiprofessional team (clinical lead, matron, all grades of medical staff, all grades of nursing staff, medical and nursing students, emergency pharmacist, domestic violence team, general manager, practice development team and alcohol liaison nurse). The results demonstrated that staff mostly supported the new morning handover structure. It was thought to be a very useful source of information in regards to departmental and trust updates in a multiprofessional forum (75 staff members). Staff members felt it was a forum for interprofessional education (65 staff members). Also, majority agreed that it improved patient care and operational issues within the department and trust wide (67 staff members). Conclusions: Our unique morning handover structure ensures patient safety as well as appropriate transfer of information and responsibility to all involved with the care of patients in the Emergency Department. It offers the opportunity for multiprofessional learning, encourages team work and improves the operational processes within the Emergency Department.